Evaluasi Tata Kelola Teknologi Informasi Menggunakan Kerangka Kerja Cobit 5 Pada Gelato Secrets - Ayu Manik Dirgayusari; Desak Made Dwi Utami Putra; Ni Wayan Rika Andini (Faculty of Computer Science, University of Jember, 2021)
Many people have benefited from the use of information technology, one of which is in the trade business sector. One company that is engaged in manufacture that utilizes information technology in its operational processes is Gelato Secrets. Its efforts to support business goals have been supported by an Information System (SI) which is still relatively new to be implemented in Gelato Secrets, namely the Odoo application that supports the sales process in each outlet. To evaluate the maturity level of information technology governance in the Odoo application, a framework is needed as a reference model to ensure the quality of IT governance in the application of the